ETIKA KEWARGANEGARAAN DALAM SERAT WULANGREH - Zuhri, Amat (Fakultas Ilmu Budaya Universitas Diponegoro, 2015)
Wulangreh is a literary work that contains piwulang (teaching) written by Pakubuwana IV about the necessities to obey institutionalized kraton (kingdom) ethics. Although parts of this Wulangreh vary, one thing that is clear is about the worship of the state, and more specifically the service to the king. The ethics and manners taught are devoted to the country and the king. Among the set of ethics that must be upheld by the citizens is the necessity for devotion to an absolute ruler without criticism. Ethics as it is based on the belief that the ruler is as representative of the Lord of all policies will always the truth.